Stability properties of non-negative solutions of semilinear symmetric cooperative systems - Imre Voros (Electronic Journal of Differential Equations, 2004)
We investigate the stability of non-negative stationary solutions of symmetric cooperative semilinear systems with some convex (resp. concave) nonlinearity condition, namely all second-order partial derivatives of each coordinate being non-negative (resp. non-positive). In these cases, we will show following [8], extending its results, that this along with some sign condition on the non-linearity at the origin yields instability (resp. stability).